The Issue of Asymmetric Information Upon the Capital Market - Olga Plesco; Ludmila Sobol (CES Working Papers, 2013)
The capital market has an important role at the micro and macro economical level, having the capacity to mobilize resources and to place them in a productive manner. The relation between accounting and capital market started to be analyzed from the middle of XXth century, when the investors started to ask more details about the companies' activity and not just general accounting values. The certainty is nowadays a part of the cost of information which is consciously assumed by the users differently in pre-crisis and crisis time. Informational asymmetry plays a double role through the participants on the capital market: positive one for those who use the lack of information of others with economic responsibility and negative when information holders use them to affect the other participants or users. This paper seeks to examine the impact of financial information on the level of the capital value of the companies in order to evaluate the influence and to establish the measures that must be applied to reduce the asymmetries between different users of that information.
Keywords: E22; M49; 330; financial information; cost of capital; information asymmetry; performance; disclosure Romania